Social Media Enabled Contract Cheating - Lancaster, Thomas (Canadian Perspectives on Academic Integrity, 2019)
The contract cheating industry, those services and individuals who are supplying students with original work for assessment, is evolving. Contract cheating companies are using enhanced marketing techniques, including social media marketing, to encourage potential customers to avail themselves of services that breach academic integrity. Social media is proving to be integral to the success of the contract cheating industry as a whole. It allows contract cheating companies to recruit academic ghost writers and other staff. In addition, social media is fuelling a black market trade in contract cheating service accounts. Potential ghost writers who would not otherwise qualify are using this hidden market to get accounts to work for contract cheating services. This paper examines the state of the contract cheating industry, paying particular attention to the role that social media has played in the industry’s development and apparent growth. The discussion of the industry is supported by example and case studies. These cover the end-to-end contract cheating process from when an essay mill is first set up, through to supplying services to students and to engaging contract cheating service workers. Examples of contract cheating and social media use of specific interest to Canadian academics and scholars are included. The paper concludes with a discussion of future challenges as well as the opportunities for academic integrity discussions. These are intended to enable academics to work with students as academic integrity partners and to enable discussions that make use of what is known about the operation of the contract cheating industry.